Changing mentalities on flooding in the Upper Rhine valley landscape. An interdisciplinary landscape study on the role of changing flood perception on the emergence of its management in the Upper Rhine valley. - Conijn, Adrianus Maria (My University, 2020)
Das Forschungsprojekt „Land unter?“ hat das Ziel die Geschichte der Hochwasserereignisse im Oberrheingraben von Straßburg bis Mannheim zu rekonstruieren. Die Arbeit präsentiert, als Teil eines interdisziplinären Projektes, eine Vielfalt an Methoden, Quellen und Daten, die in regionalem, landschaftlichem und kulturellem Kontext stehen. Die generelle menschliche Wahrnehmung von Hochflutereignissen wird dabei mit eingebunden. Darauf aufbauend, werden diverse Mentalitätskonzepte durch eine chronologische Ordnung der Kulturgeschichte entworfen. Die große Menge an historischen Daten wird hierbei berücksichtigt. Die Ergebnisse offenbaren, dass sich die Wahrnehmung des Menschen über die Zeit veränderte und, dass dadurch ebenfalls die Landschaft des Oberrheingrabens einem Wandel unterworfen war. Siedlungsstruktur, Überschwemmungen, schwierige klimatische Bedingungen erforderten Schutzmaßnahmen. Landgewinnung durch Trockenlegungen und Deichkonstruktionen war die Chance unberührte Landschaften als Ressource zu nutzen. Das veränderte sich, als sich die Technologien weiterentwickelten und der Mensch die Kontrolle über den Fluss erlangte und Flussbegradigungen durchführte. Die Arbeit stellt eine Verbindung von geophysikalischen Daten und kulturellen Narrativen dar – miteingeschlossen die subjektive Wahrnehmung in Form einer Landschaftsanalyse. Die gewonnenen Erkenntnisse über die Hochwasserereignisse im Oberrheingraben eröffnen eine wissenschaftliche Debatte über die interdisziplinäre Forschung und die Einbindung von subjektiven Landschaftswahrnehmungen.

The interdisciplinary project ‘Land Unter?’ aims to develop a history of flooding for the Upper Rhine valleyfrom Strasbourg to Mannheim. A multidisciplinary variety of methods, sources, and data is used andcombined into an interdisciplinary landscape study. By arranging a chronological cultural biography of theperception of flooding, mentality templates were defined. The great variety of data has been fit within thesetemplates. The results show how the human perception changed over time, affecting the landscape of theUpper Rhine valley.The mentality templates shift from settlement on healthy and save terrace rims, to self-sufficiency for greaterwealth. When flooding is seen as a sign for new disasters, the church offers protection of the property.Although, ongoing flooding and harsh climate conditions during the 10th century demanded a new approachand the necessity of actions on flood management had to be taken by the church. Draining and dikeconstruction provided the possibility to extend lands and use former natural wilderness as a resource. Whilean increasing number of farmers got their own land, they were also obliged for the protection of theirproperty. These were the results in a period when villages in the Upper Rhine valley had a hard time tosurvive natural vagaries. However, when techniques improved humans gradually gained total control of theriver, resulting in the Tulla-rectification in the early 19th century. Only recently, a more harmoniousinteraction with nature seems to gain support.In order to see whether this theoretical timeline of mentalities holds up in practice, two case studies havebeen conducted. The first case study in Speyer did not result in prove of flood protection measures byBishop Benno in the 11th century. However, bringing together geophysical data and historical sourcesprovided some new prove on the course of the Rhine around Speyer during the early medieval period.Another case study in Ottersdorf near Rastatt included an archaeological excavation of a medieval dike. Thisdike has been dated back to the 11th century by humins and humin acids of the former surface layer. This issignificantly earlier than other dikes in Western Europe and on top of it, it can be linked to the expansionof arable fields, which also seems quite early for offensive dike construction.Altogether, including the perception into a landscape study, this work provides a good link betweengeophysical data and cultural narratives. The case studies additionally confirmed and challenged severaloutcomes. Furthermore, this research has overcome the lack of knowledge on flooding in the Upper Rhinevalley and additionally added to the academic debate on interdisciplinary research and inclusion of subjectivelandscape perception.
Hochwasser-Mentalität im Oberrheintal. Eine interdisziplinäre Landschaftsstudie zur Rolle der sich verändernden Hochwasserwahrnehmung bei der Entstehung des Hochwassermanagements im Oberrheintal.
Keywords: Hochwasser; Hochwasserschutz; Hochwasserrisiko; Flusssystem; Überflutung; Wechselwirkung; Landschaftswandel; Landschaftsanalyse; Wahrnehmung; Landschaftsstruktur; Siedlungsgeschichte; Landschaftsgeschichte; Mensch-Umwelt-System